2011
DOI: 10.1039/c1cc12929e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical engineering of Mycobacterium tuberculosis dodecin hybrids

Abstract: The suitability for chemical engineering of the highly symmetrical Mycobacterium tuberculosis dodecin was investigated, its inner cavity providing a large compartment shields introduced compounds from bulk solvent. Hybrids were obtained by S-alkylation of cysteine mutants and characterized by spectroscopic methods, including the crystal structures of wild type and biohybrid dodecins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…If such an electron transfer occurs, the spectrum should show the absorption characteristics of a cationic tryptophan radical, expected around 560 nm (38,39) and of an anionic flavosemiquinone around 510 nm (40 -42). For RfbP from chicken egg white, an electron-transferred state consisting of a cationic tryptophan radical and a flavosemiquinone has already been identified which shows spectral characteristics as observed for dodecin (7,17). However, a remarkable difference between the reported data on chicken RfbP is the positive signal around 500 nm, which is not synchronized with the positive signal at longer wavelengths, and decays more slowly.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…If such an electron transfer occurs, the spectrum should show the absorption characteristics of a cationic tryptophan radical, expected around 560 nm (38,39) and of an anionic flavosemiquinone around 510 nm (40 -42). For RfbP from chicken egg white, an electron-transferred state consisting of a cationic tryptophan radical and a flavosemiquinone has already been identified which shows spectral characteristics as observed for dodecin (7,17). However, a remarkable difference between the reported data on chicken RfbP is the positive signal around 500 nm, which is not synchronized with the positive signal at longer wavelengths, and decays more slowly.…”
Section: Resultscontrasting
confidence: 43%
“…Structures revealed a dodecameric fold, providing six identical binding pockets, which each enables binding of two antiparallel arranged flavins between two tryptophan residues building an aromatic tetrade arrangement ( Fig. 1A) (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…There are fewer complexes with an odd number of subunits than there are complexes with an even number of subunits. Examples shown are dodecin (PDB ID 2yiz [60]), ferritin (PDB ID 1aew [61]), and Paramecium bursaria Chlorella virus type 1 (PDB ID 1m4x [62]).…”
Section: Trendsmentioning
confidence: 99%
“…[1] Unique to dodecins is the binding mode of the flavins, where two flavins are bound between two tryptophans forming an aromatic tetrad in the binding pocket. [1,13,51] The crystal structure of HsDod revealed that the dodecin monomers have a β1α1β2β3 topology resulting in single αhelix partly enwrapped by a three stranded antiparallel β-sheets. [1] So far, all studied dodecins share this structure (see Figure 5).…”
Section: The Dodecin Protein Familymentioning
confidence: 99%
“…HhDod: The dodecin of H. halophila (PDB ID: 2VXA) [7] . MtDod: The dodecin of M. tuberculosis (PDB ID: 2YIZ) [51] . ScDod: The dodecin of Streptomyces coelicolor (PDB ID: 6R1E) [53] .…”
Section: The Dodecin Protein Familymentioning
confidence: 99%